Analyzing the Expression of Complementing in Harry Potter the Movie By Using Grice’s Cooperative Principles: A Contextual Supplementary Material - Rizkiyah, I; Rezky Winanda, E (KnE Social Sciences, 2019)
In Indonesia, English is a foreign language which means that the language is only used for academic purposes. As the result, the students lack of English exposure outside the classroom and teacher becomes the only model of learning English. In addition, the material that the teachers use mainly textbook which the content is limited and not contextual. To overcome the problem, teachers use authentic materials to bridge the gap between the real language use and the prescriptive ones. Authentic materials have some advantages such as providing various contextual and natural expressions but at the same time carries non academic language that is hard to understand. It is the teachers’s job with his/her discourse competence to decipher the message for the students and uses it as the models of language expression. It is important to find different kinds of natural language models for the students in order to help them use the language naturally and appropriately. Therefore, this paper will analyze compliment and compliment response expressions in Harry Potter the movie by using Grice’s Cooperative principle in order to find more examples of these expressions and to provide alternative materials in speaking class. Keywords: implicature, authentic materials, compliments and compliment responses, pedagogical implication